2017
DOI: 10.1097/mib.0000000000001108
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols in the Aetiology of Crohnʼs Disease and Ulcerative Colitis—A Multicenter European Prospective Cohort Study (EPIC)

Abstract: The data supports a potential role of flavones and resveratrol in the risk of developing CD; future aetiological studies should investigate these dietary components and further examine the potential for residual confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Experimental evidence has suggested that polyphenols prevent colitis by inhibiting the biological process of oxidative stress and the associated damage to DNA, lipids, and proteins. The mechanism was to study proinflammatory proteins by affecting the mitogen‐activated protein kinase and transcription factor NF‐κB signaling pathway . In the present study, we found that the administration of polyphenols increased the biochemical parameters SOD and GSH‐Px in the serum and decreased MPO and NO in colon tissue.…”
Section: Discussionsupporting
confidence: 54%
“…Experimental evidence has suggested that polyphenols prevent colitis by inhibiting the biological process of oxidative stress and the associated damage to DNA, lipids, and proteins. The mechanism was to study proinflammatory proteins by affecting the mitogen‐activated protein kinase and transcription factor NF‐κB signaling pathway . In the present study, we found that the administration of polyphenols increased the biochemical parameters SOD and GSH‐Px in the serum and decreased MPO and NO in colon tissue.…”
Section: Discussionsupporting
confidence: 54%
“…95,152 Indeed, as part of the IBD European Prospective Cohort Study (IBD-EPIC study), many dietary factors have been associated with IBD onset. [153][154][155][156] Milk consumption was shown to be potentially associated with a decreased risk of developing CD (P = 0.23 for CD) but not with UC (P = 0.60), 154 whereas a role of flavones and resveratrol in the risk of developing CD was also observed. 155 The IBD-EPIC study findings also support a role for dietary linoleic acid in the etiology of UC.…”
Section: Table 1: Continuedmentioning
confidence: 99%
“…[153][154][155][156] Milk consumption was shown to be potentially associated with a decreased risk of developing CD (P = 0.23 for CD) but not with UC (P = 0.60), 154 whereas a role of flavones and resveratrol in the risk of developing CD was also observed. 155 The IBD-EPIC study findings also support a role for dietary linoleic acid in the etiology of UC. 155 In this cohort, obesity, as measured by body mass index (BMI), was not associated with the development of UC or CD.…”
Section: Table 1: Continuedmentioning
confidence: 99%
“…Milk and milk product consumption was observed to be potentially related with a low risk of developing CD (p = 0.23) but not for with UC (p = 0.60) [224], whereas a role of flavones (C 15 H 10 O 2 ) and resveratrol (C 14 H 12 O 3 ) in the risk of triggering CD was also shown [225]. The IBD-EPIC study results also indicate dietary role for linoleic acid in the etiopathogenesis of UC [225]. According to this calculated study cohort, overweight, as measured by BMI (body mass index), was observed not consociated with the etiopathogenesis of either UC or CD, respectively [226].…”
Section: Dietary/nutritionmentioning
confidence: 91%
“…Intestinal mucosal microbiota composition is dependently influenced and modified by diet [221,222]. According to the IBD-EPIC (IBD European Prospective Cohort) Study, several dietary factors have been found to be related with IBD onset [223][224][225][226]. Milk and milk product consumption was observed to be potentially related with a low risk of developing CD (p = 0.23) but not for with UC (p = 0.60) [224], whereas a role of flavones (C 15 H 10 O 2 ) and resveratrol (C 14 H 12 O 3 ) in the risk of triggering CD was also shown [225].…”
Section: Dietary/nutritionmentioning
confidence: 99%